Influence and originality in Michael Quinn Patton's "Utilization-Focused Evaluation" - Moleko, Motheo Precious (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2011.